Investigations of Multiphysics Models on a Megawatt-Level Heat Pipe Nuclear Reactor Based on High-Fidelity Approaches - Zhang, Junda; Li, Tao; Shen, Zhirui; Li, Xiangyue; Xiong, Jinbiao; Chai, Xiang; Liu, Xiaojing; Zhang, Tengfei (Nuclear science and engineering, 2024)
This work describes the research of high-fidelity multiphysics models for the MegaPower nuclear reactor, a megawatt-level heat pipe reactor. Combining the Monte Carlo neutronics model, the heat pipe analysis model, the fuel analysis model, and the thermoelasticity model produces the Multi-Physics Coupling code for Heat pipe nuclear reactors (MPCH) code platform. Using the heat pipe analysis model, a database of heat pipes is generated to save computing costs. Comparison is made among four calculating modes with differing degrees of coupling. It was discovered that the thermal expansion effect reduces core reactivity by 537 ± 11 pcm and the temperature feedback coefficient by 61%. With the incorporation of the heat pipe module, a temperature difference arises between the wall of heat pipes, which can reach a maximum value of 80 K at steady state. Simultaneously, the global fuel rod temperature difference increases from 34 K (under the assumption of uniform heat pipe wall temperature) to 93 K, and the monolith temperature variance increases from 34 to 108 K. At the periphery of the monolith, the increased temperature variation causes a monolithic stress of 188.6 MPa. To further investigate the safety of the reactor, three-heat-pipe-failure scenarios are evaluated. The heat pipe analysis model reveals that a single heat pipe failure results in a monolith peak temperature of 1046 K, giving a maximum monolith stress of 237 MPa. The maximum monolith stresses and temperatures for the two-heat-pipe-failure scenario and the three-heat pipe-failure scenario are 330 MPa/1128 K and 471 MPa/1233 K, respectively. In steady-state operation, the stresses exceed the yield tensile strength (131MPa) whereas those generated by the failure of three heat pipes exceed the ultimate tensile strength (345 MPa) in high temperature. These results illustrate the necessity of including coupled multiphysics models into the design and safety evaluation of innovative nuclear reactors.